Water depth and feed pellet type effects on growth and feed utilization in the rearing of green turtle (Chelonia mydas Linnaeus, 1758) - Songnui Anida; Thongprajukaew Karun; Kanghae Hirun; Satjarak Jirapan; Kittiwattanawong Kongkiat (Aquatic Living Resources, 2017)
The rearing of green turtles (Chelonia mydas Linnaeus, 1758) before their release to natural habitats has been practiced in several countries, whereas little information is available for inferring optimal husbandry protocols. This study aimed to improve the growth performance and feed utilization of post-hatching green turtles by varying the water depth (15 or 30 cm) and feed pellet type (sinking or floating pellets). The 20-day-old turtles (23.49 ± 0.02 g initial body weight) were subjected to a 2 × 2 factorial experiment (3 replications with 5 animals per tank) over a two-month duration. Growth, feed utilization, fecal digestive enzymes and hematological parameters were recorded to evaluate the effects of different treatments. No mortality was observed in any treatment group. Turtles reared in 15 cm water depth and fed with floating pellets exhibited superior growth (specific growth rate 2.76% body weight day−1) and feed utilization (feeding rate 1.42% body weight day−1, feed conversion ratio 0.61 g feed g gain−1, protein efficiency ratio 3.76 g gain g protein−1), relative to the other treatments. This treatment improved the utilization of nutrients by modulating trypsin specific activity but had no negative effects on hematological characteristics. Overall these findings indicate that the rearing program of post-hatching green turtles should be run with about 15 cm water depth and the preferred type of feed is floating pellets. These preferred conditions can also be applied in public displays, such as zoos or aquaria.